Western-Pontic Culture Ambience and Pattern - Merlini, Marco (De Gruyter, 2017)
'Western-Pontic Culture Ambience and Pattern' is dedicated to the memory of Eugen Comsa, an archaeologist whose work created the foundation of the Northern Balkan prehistory and was essential for the contemporary view of the prehistory of the North-western Pontic region. The volume brings together researchers in the field of Circumpontic archaeology from the Neolithic to the Iron Age period. The content of the volume is offered to students and scholars who seek a deeper understanding of the prehistory of the Western Pontic region, in particular the Balkans in their Eurasian context and more broadly to enhance the scholarly collections of academic, educational, public and private libraries throughout the world.